Projeto de redes de sensores sem fio heterogêneas utilizando os conceitos de redes small word - Daniel Ludovico Guidoni (2011)
A typical Wireless Sensor Network (WSN) assumes a homogeneous set of nodes in terms of capabilities. However, this kind of network suffers from poor fundamental limitations of latency during the data communication. Another model of WSN assumes a heterogeneous set of nodes with different capabilities (especially in terms of communication range and energy reserves) called Heterogeneous Sensor Networks(HSN). In this work, we propose small world models to design Heterogeneous Sensor Networks (HSNs). The first model takes into account the communication pattern of this network to create shortcuts directed to the monitoring node, decreasing the data communication latency. The endpoints of these shortcuts are nodes with more powerful communication range and energy reserves to support the long communication range. We evaluate the proposed model and show that they present the same small world features (average path length and clustering coefficient) observed in the literature models. When the shortcuts are created toward the sink node, with a few number of powerful sensors, the network presents better small world features and interesting tradeoffs between energy and latency in the data communication when compared to the literature model. Also, we evaluate the resilience of the proposed model considering general and specific failures and, in both cases, the proposed model is more robust and presents a graceful degradation of the network latency, which shows the resilience of those models. However, the long range communication used to create a shortcut causes a high interference in the wireless channel. For this, we present a model that uses multi-interface and multi-channel capability of the MAC layer to reduce collisions during the data communication. Simulation results showed that when the shortcuts are directed to the sink node and assigned to a different wireless channel, collisions and latency are reduced. We also proposed a framework based on the small world concepts to design heterogeneous sensor networks with QoS. The framework uses three different topologies to provide QoS in sensor networks. Each topology has its own objectives related to latency during communication and energy consumption. Simulation results showed that the proposed framework can reduce latency and energy consumption compared to the topology used in the literature to provide QoS in sensor networks.